PELATIHAN STRATEGI PEMASARAN UMKM PERHOTELAN NON BINTANG DI BANJAR KELOD - BALI: PELATIHAN STRATEGI PEMASARAN UMKM PERHOTELAN NON BINTANG DI BANJAR KELOD - BALI - Septiani, Mira; Iketut Edy Mulyana (Jurnal Pengabdian Masyarakat Sabangka, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in the hospitality industry such as hotels, villas, bungalows, and others often face challenges in determining effective marketing strategies both offline and online. This community service aims to enhance understanding and knowledge about applying appropriate marketing strategies for non-star hospitality industry. The methods used include socialization, practical marketing strategies, and evaluation. The partners in this activity consist of 15 owners or managers of MSME hospitality industries in Banjar Kelod, Lembongan Village, Nusa Penida District, Klungkung Regency, Bali. This training activity successfully increased partners' knowledge in implementing appropriate marketing strategies and supported partners to have competitiveness in the market.